The Glass Town game - Valente, Catherynne M., 1979- (Margaret K. McElderry Books, an imprint of Simon & Schuster, 2017)
"Inside a small Yorkshire parsonage, Charlotte, Branwell, Emily, and Anne Brontë have invented a game called Glass Town, where their toy soldiers fight Napoleon and no one dies. This make-believe land helps the four escape from a harsh reality: Charlotte and Emily are being sent away to a dangerous boarding school, a school they might not return from. But on this Beastliest Day, the day Anne and Branwell walk their sisters to the train station, something incredible happens: the train whisks them all away to a real Glass Town, and the children trade the moors for a wonderland all their own."--Book jacket flap.